Ответ:
Пошаговое объяснение:
a)
0,6(x - 2) = 0,5(2 - x) - 5,5
0,6x - 1,2 = 1 - 0,5x - 5,5
0,6x - 1,2 = -4,5 - 0,5x
0,6x + 0,5x = -4,5 + 1,2
1,1x = -3,3
x = -3,3 : 1,1
x = -3
===============
б)
(4+x)/3 = (x+2)/2
3(x+2) = 2(4+x)
3x + 6 = 8 + 2x
3x - 2x = 8 - 6
x = 2
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
a)
0,6(x - 2) = 0,5(2 - x) - 5,5
0,6x - 1,2 = 1 - 0,5x - 5,5
0,6x - 1,2 = -4,5 - 0,5x
0,6x + 0,5x = -4,5 + 1,2
1,1x = -3,3
x = -3,3 : 1,1
x = -3
===============
б)
(4+x)/3 = (x+2)/2
3(x+2) = 2(4+x)
3x + 6 = 8 + 2x
3x - 2x = 8 - 6
x = 2